Representation of circulation patterns by orthogonal polynomials with application to specification of weather from them - BEDI , H. S.; GUPTA, R. K. (MAUSAM, 1972)
A technique for representation of atmospheric circulation patterns as a linear combination of simple patterns given by a set of Tschebyscheff orthogonal polynomials has been examined. This enables 5-day mean 700 mb circulation systems over Indian region to be parameterized in terms of a limited number of circulation indices which can be utilized for developing objective statistical relationships between atmospheric circulation systems and the weather.